Expression of P53, PTEN and S100A4 in invasive ductal breast cancer and the clinical significance - Gang, Z; Zhong, L; Xiao-meng, L; Jun-hua, Z; Yong, C; Xing, Z (Journal of Chitwan Medical College, 2017)
Objective: To investigate the expression level of P53, PTEN and S100A4 in invasive ductal breast cancer and the clinical significance. Methods: SP immunohistochemical and Western blot analysis were used to detect the expression of P53, PTEN and S100A4 protein in invasive ductal breast cancer, adjacent tissues and benign breast lesions. Results: Immunohistochemical results showed that the positive rates of P53 and S100A4 in invasive ductal breast cancer were 47.69% and 56.92%, which were significantly higher than that in benign breast lesions 16.00% and 22.00% respectively (P